“Migration Crisis” and the Far Right Networks in Europe: A Case Study of Serbia - Lažetić, Marina (Journal of Regional Security, 2018)
During the “migration crisis” Serbia has been a transit country. However, several thousands of migrants and refugees remained “stuck” in the Western Balkans after the closure of the Balkan Route, and issues related to their potential integration provided a platform for Ser- bian far right movements and parties to establish new and stronger relationships with their Eu- ropean counterparts. This changed the far right landscape in the Western Balkans and allowed anti-European narratives to strengthen. This paper identifies the “new far right” which is on the rise in Serbia, and its relationships with the larger network of European far right movements. Based on field interviews and social media content analysis, the paper draws a conclusion that if the EU fails to take a more active role in making integration an attractive option for the Western Balkan countries, the rise of far right movements in the region could present a serious security threat.